The 25 February 2021 military strikes and the 'armed attack' requirement of self-defence: from 'sina qua non' to the point of vanishing?. (2nd January 2022) - Henderson, Christian
ABSTRACT: Following a rocket attack that occurred at Erbil airport in Iraq, President Biden authorised the first use of military force since becoming President on 25 February 2021. This was legally justified on the basis of self-defence. On the face of it this seemed an innocuous justification. Yet, this article argues that through both downplaying the treaty source of the right of self-defence and its express requirement for an armed attack, as well as promoting a contextual and enabling form of necessity, the Biden administration's military action and ensuing strategy of legal justification place question marks over the meaning of, and even the requirement for, an armed attack. However, seeing the 25 February incident in the context of broader US and other state practice, while various attempts at diluting this requirement and the interpretation provided to it by the International Court of Justice have been sustained, others have clearly not.